Influência do tempo de ciclo no processo de nitrificação em reator em bateladas sequenciais e microfauna observada - Lazzereis, Sheila Aparecida Fritsch (2016)
Refrigerators derivatives agroindustrial waste and slaughterhouse pigs have great load particularly nitrogen and phosphorus nutrients, and high concentration of solids and organic matter. The nitrogen in the aquatic environment can be found under the main ways that are organic nitrogen, ammonia, nitrite and nitrate in addition to molecular nitrogen. The purpose of the removal of nutrients is to ensure the quality of the effluent and protect water bodies that receive these evictions. Removal of nitrogen by biological treatment performed in sequencing batch reactor (SBR), in operation creates conditions that favor then nitrification denitrification. The reactors are operated in sequential batch variations in a single activated sludge tank where all the steps and reactions occur sequentially over time by the present Microfauna activity. To this end, this study aimed to evaluate the nitrification process in a reactor sequencing batch containing free biomass and fed slaughterhouse wastewater and pig refrigerator. The tests were conducted with the objective of evaluating the efficiency of nitrification in sequencing batch reactor, the conversion of ammonia nitrogen into nitrite and nitrate and correlating the presence of Microfauna with the efficiency of the treatment. The reactor study was efficient for the removal of ammonia nitrogen pre-treated wastewater anaerobically, a slaughterhouse and refrigerator pigs showed better efficiency in the nitrification process and removal of organic matter with the cycle time (CT) 48 hours, 63.6% for removing ammonia nitrogen and qualitative microscopic visualization of microfauna can be related to an immediate diagnosis of the conditions of RBS treatment system and its efficiency.